Peningkatan Pelayanan, Pemasaran dan Keamanan Bagi Penyedia Jeep Wisata - Juhari Sasmito; Anang Sya’roni (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2017)
Since the eruption of Merapi mountain in 2010 the condition of tourism in Sleman Regency has decreased drastically enough. Likewise it happens in the leading tourist destination of Kaliurang tourism area. Post-eruption of Merapi, Sleman Regency Government do image recovery tourism by holding activity “Sleman Bangkit” which bear enough sweet with start recovery condition of tourism as before. Since starting to recover in 2012 raises the idea for the youth in Kaliurang to create a tourist attraction in the form of jeep advanture that visited the attractions affected by the eruption of Merapi or which emerged after the eruption of Merapi. The activities of the jeep provision of the tour until now has been going pretty well but still encountered obstacles such as: the absence of a unified teamwork in providing services to tourists, not well understood about the service oriented to customer satisfaction and safety of tourists, skills in operational jeep tourism, and not optimal use of the internet as a media campaign. From these emerging problems, the community service program is designed to find solutions in the form of outbound training to cultivate solid teamwork, tourism service oriented to the satisfaction of tourists, safe driving training and provide protection to passengers, and interactive website creation to serve as media promotion and also for booking tour package adventure. Community service activities that have been done to produce outcomes include: attractive uniforms, brochures / leaflets, and website “Kaliurang Advanture”, and website “Yoes Advanture”. Similarly, outbound training activities have been conducted to increase togetherness and training in driving skills to create a sense of security for both drivers and tourists. After the community service program is completed then it can improve operator performance in providing services to tourists.Keywords: service, marketing, security, tour jeep.